Pioneering Conservation in Alaska - Ross, Ken, 1937- (Book collections on Project MUSE., 2006)
Designed as a companion to his "Environmental Conflict in Alaska" (2001), which presented the environmental issues of Alaska's statehood period, the newest study by Ross provides an in-depth view of the resource management controversies in Alaska up to statehood in 1958. Ross's chapters on predator control, when wildlife managers offered bounties not just for wolves but for eagles, and another on attempted translocations of ungulates, reveal astounding efforts to manipulate ecosystems. Especially useful is his history of the successful efforts to preserve the Arctic National Wildlife Refuge.